Lean back or lean in? Exploring social loafing in human–robot teams - Cymek, Dietlind Helene; Truckenbrodt, Anna; Onnasch, Linda (Frontiers in Robotics and AI, 2023)
Thanks to technological advances, robots are now being used for a wide range of tasks in the workplace. Often, they are introduced as team partners to assist workers. This teaming is typically associated with positive effects on work performance and outcomes. However, little is known about whether typical performance-reducing effects that occur in human teams also occur in human-robot teams. For example, it is not clear whether social loafing, defined as lower individual effort on a task performed in a team compared to a task performed alone, can also occur in human-robot teams. We investigated this question in an experimental study in which participants worked on an industrial defect-inspection task that required them to search for manufacturing defects on circuit boards. One group of participants worked on the task with a robot team partner, receiving boards that had already been inspected by the robot, while the other group worked alone. The dependent behavioral measures of interest were effort expended, operationalized as inspection time and area inspected on the board, and defect-detection performance. In addition, subjects rated their subjective effort, performance, and perceived responsibility for the task. Participants' objective and subjective effort were high in both groups and did not differ significantly. However, participants working in a team with the robot detected significantly fewer board defects, suggesting that participants might have searched the boards less attentively.